THERMODYNAMIC AND THERMOPHYSICAL ASSESSMENT OF HYDROCARBONS APPLICATION IN HOUSEHOULD REFRIGERATOR - Almeida, I. M. G.; Barbosa, C. R. F.; Fontes, F. A. O. (Revista de Engenharia Térmica, 2010)
The research efforts and development in the refrigeration and air conditioning sector applied to the use of natural refrigeration fluids is not associated only with the need to preserve the environment alone, but has great importance with regard to the latent need for energy efficient equipment. With this perspective, the present study deals with the thermodynamic evaluation of the use of hydrocarbons refrigerants in household refrigeration systems that utilize HFC134a as a working fluid. A theoretical-computational analysis was developed for R134a, propane (R290) and the selected mixtures (R290/R600a 60%/40%, R290/R600a/R134a 40%/30%/30% and R600a/R290 50%/50%) in the standard refrigeration cycle ASHRAE, using the thermodynamic and thermophysical properties provided by the REFPROP 6.0 software. The results of computational simulations between the fluids were compared to find the evidence of the best alternative to HFC134a. In this sense, it was observed that the hydrocarbons reduced the levels of pressure on the condenser and evaporator, along with smaller compression tasks necessary in the system, owing to the thermo-physical properties privileged in these fluids. The use of these fluids is also proportionate to lower temperatures of compressor discharge, increasing the life of this highly valuable component of the system.